Divorce and Muslim women - Moinuddin, S. A. H. (Jaipur: Rawat Publications, 2000)
With special reference to West Bengal, India.
"Published under the auspices of Vidyasagar University, Midnapur (W.B.)."
Includes bibliographical references (p. [173]-183) and index.
Keywords: WOMEN IN ISLAM; DIVORCE (ISLAM LAW)